Population of Long-tailed Macaque (Macaca fascicularis) at several habitat conditions in Jambi Province, Indonesia - FEVI MAWADHAH PUTRI; AHMAD SYUKRON PRASAJA; PUTRA TRI KURNIAWAN; YULI SULISTYA FITRIANA; SIGIT WIANTORO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putri FM, Prasaja AS, Kurniawan PT, Fitriana YS, Wiantoro S. 2024. Population of Long-tailed Macaque (Macaca fascicularis) at several habitat conditions in Jambi Province, Indonesia. Biodiversitas 25: 3254-3262. The Long-Tailed Macaque (LTM; Macaca fascicularis (Raffles, 1821)) plays a crucial role in forest regeneration through seed dispersal. However, recent ecological shifts have impacted their survival, pushing them to expand into human settlements. This study aims to investigate the current LTM population across various habitats in Jambi Province. Data on the number, gender, age, sex ratio, population density, and habitat conditions were collected. Sampling was conducted at sites previously reported for LTM-human conflicts and potential harvesting areas. The study employed point counts at 12 locations and line transects at 2 locations across five administrative regions. The results indicated a higher female-to-male ratio, with the largest population of LTMs (n = 923) found at PT Perkebunan Nusantara (PTPN) VI Bunut, followed by the Berbak River (n = 740). The smallest populations were observed at Mendalo Darat (n = 74) and Talang Bakung (n = 76). The line transect method was employed to estimate the population density at PTPN VI Bunut, resulting in approximately 0.742 individuals per hectare, translating to an estimated population of 3,436 individuals. At Muaro Jambi Temple, the density was approximately 0.826 individuals per hectare, with an estimated population of 1,884. Habitat-type Watersheds had the highest average number of individuals (713.5), followed by agricultural land (407.33), indicating that these habitats have a high carrying capacity for Long-tailed Macaques due to the availability of water and food. One limitation of this study is the single-instance sampling in 2023, which underscores the need for further research to capture population dynamics fully. The urgency and importance of this topic cannot be overstated.